2016
DOI: 10.1038/cr.2016.102
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of anti-PD-L1 monoclonal antibody avelumab for tumor therapy

Abstract: Monoclonal antibodies (mAbs) blocking immune checkpoint molecules, especially programmed cell death 1 (PD-1) and its ligands programmed cell death 1 ligand 1 (PD-L1) and ligand 2 (PD-L2), are currently been investigated for treatment of various tumors [1-3]. PD-L1 and PD-L2 are usually upregulated on the surface of multiple tumor cells to mediate immune tolerance through the interaction with inhibitory PD-1 molecule [4]. Thus, blocking PD-1/PD-Ls interaction has brought promising future for tumor immunotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
127
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(132 citation statements)
references
References 10 publications
2
127
0
3
Order By: Relevance
“…This is consistent with the general observation that the LCDR2 of antibodies is often not involved in antigen binding. The previously reported structures of PD-L1 in complex with BMS-963559 or avelumab demonstrated that these two antibodies similary involved only five of the six CDRs in the interaction with PD-L1, leaving LCDR2 without any binding to PD-L1 38, 39 .
Figure 1Crystal structures of PD-1 in complex with atezolizumab and durvalumab. ( a ) Ribbon representation of the complex structure of PD-L1/atezolizumab Fab fragment.
…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This is consistent with the general observation that the LCDR2 of antibodies is often not involved in antigen binding. The previously reported structures of PD-L1 in complex with BMS-963559 or avelumab demonstrated that these two antibodies similary involved only five of the six CDRs in the interaction with PD-L1, leaving LCDR2 without any binding to PD-L1 38, 39 .
Figure 1Crystal structures of PD-1 in complex with atezolizumab and durvalumab. ( a ) Ribbon representation of the complex structure of PD-L1/atezolizumab Fab fragment.
…”
Section: Resultsmentioning
confidence: 95%
“…5) 34, 3739 .
Figure 5Comparison of the PD-L1 interactions with the receptor PD-1 and anti-PD-L1 antibodies. ( a ) Structure of PD-L1 (pale blue) in complex with PD-1 (orange) and the PD-1 binding site (orange) on the surface of the IgSF V-set domain of PD-L1.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystal structures of the anti-PD-1 pembrolizumab Fab fragment complexed with hPD-1 and the anti-PD-L1 avelumab single chain Fv fragment (scFv) complexed with hPD-L1 have been determined by Na et al (2016) and our group, revealing the molecular basis of therapeutic antibody-based immune checkpoint therapy for tumors (Liu et al, 2016; Na et al, 2016). The interaction of pembrolizumab with hPD-1 is mainly located on two regions: the flexible C’D loop and the C, C’ strands.…”
Section: Structural Basis Of Therapeutic Antibody Interventionmentioning
confidence: 99%
“…Structural analysis of the interaction of avelumab with hPD-1 reveals that avelumab utilizes both V H and V L to bind to the IgV domain of PD-L1 on its side (Liu et al, 2016). The V H of avelumab dominates the binding to hPD-L1 by all three complementarity determining regions (CDR) loops, while V L contributes partial contacts by the CDR1 and CDR3 loops, leaving V L CDR2 without any binding to hPD-L1 (Fig.…”
Section: Structural Basis Of Therapeutic Antibody Interventionmentioning
confidence: 99%